Assessment of arising problems, risks and impacts when using high CO2, low Btu gas for power generation - Thai, Vo Hong; Hoa, Nguyen Tan; Bich, Vu Huy (Petrovietnam Journal, 2016)
The combined cycle power plants of Vietnam such as Ca Mau 1 and 2, Nhon Trach 1 and 2, and Phu My are using low CO2 gas (< 8%) from the Nam Con Son and PM3-CAA gas resources. In the future, the new power plants will have to use high CO2, low Btu gas from Block B-O Mon (CO2 20%, LHV 35MJ/sm3), and central region (CO2 30%, LHV 20MJ/sm3) gas resources. This article presents some assessments of arising problems, risks and impacts when using high CO2, low Btu gas for power generation.